Clephas, C.; Stergiou, P.; Tyreman, H.; Katz, L. - Clephas, C.; Stergiou, P.; Tyreman, H.; Katz, L. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
Competition results analysis are an increasingly important tool for national federations to compare and understand the performance of their own athletes compared to their competitors all over the world. Because of this, performing competition results analysis is becoming more important.